2009
DOI: 10.1073/pnas.0902030106
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of fast electrons

Abstract: A chemicurrent is a flux of fast (kinetic energy տ 0.5؊1.3 eV) metal electrons caused by moderately exothermic (1؊3 eV) chemical reactions over high work function (4؊6 eV) metal surfaces. In this report, the relation between chemicurrent and surface chemistry is elucidated with a combination of top-down phenomenology and bottom-up atomic-scale modeling. Examination of catalytic CO oxidation, an example which exhibits a chemicurrent, reveals 3 constituents of this relation: The localization of some conduction e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 42 publications
1
39
0
Order By: Relevance
“…As shown in Figure 10a, since the work function of metal Au (Φ m = 4.8 eV) is smaller than that of semiconductor TiO 2 (Φ s = 5.1 eV) [70], the electrons can diffuse from the metal into the semiconductor when the two phases are in contact [71,72]. This electron transfer was called "hot-electron flow" [56,57,[73][74][75] or "chemicurrent" [76][77][78], which usually happened in exothermic catalytic reactions [56,57,[73][74][75] and low-energy reactions [74] or even nonthermal directions [75]. For example, it has been reported that electron excitation was also involved in atomic/molecular adsorption processes [73,77,78].…”
Section: Proposed Electron Flow Processmentioning
confidence: 99%
“…As shown in Figure 10a, since the work function of metal Au (Φ m = 4.8 eV) is smaller than that of semiconductor TiO 2 (Φ s = 5.1 eV) [70], the electrons can diffuse from the metal into the semiconductor when the two phases are in contact [71,72]. This electron transfer was called "hot-electron flow" [56,57,[73][74][75] or "chemicurrent" [76][77][78], which usually happened in exothermic catalytic reactions [56,57,[73][74][75] and low-energy reactions [74] or even nonthermal directions [75]. For example, it has been reported that electron excitation was also involved in atomic/molecular adsorption processes [73,77,78].…”
Section: Proposed Electron Flow Processmentioning
confidence: 99%
“…The inverse of DEA to CO 2 , i.e. associative detachment, is thought to be important in the catalytic oxidation of CO on a metal surface [7]. In light of its fundamental importance to the understanding of such processes, it is noteworthy that the electronic structure of CO 2 and its metastable anions has not been completely characterized.…”
mentioning
confidence: 99%
“…99 Acid catalysis represents a unique chemistry that relies on charge transfer via protons and molecular ions, and many similarities appear to exist between SMSI and acid-base catalysis. The evolution of this work that began by measuring chemically induced charge flow at the oxide-metal interface [100][101][102] is quickly leading to a molecular level study of acid catalyzed chemistry with a focus on understanding the close relationship between charge flow and catalytic selectivity. Specifically, it is clear that a fundamental understanding of catalyst selectivity is closely related to understanding the flow of charge between various active sites on a catalyst.…”
Section: Methodsmentioning
confidence: 99%